1992
DOI: 10.1002/ar.1092330315
|View full text |Cite
|
Sign up to set email alerts
|

Localization of 5‐hydroxytryptamine‐like immunoreactive cells and nerve fibers in the rat female reproductive system

Abstract: The presence of 5-hydroxytryptamine (5-HT)-like immunoreactivity (IR) was studied in the rat female reproductive system using polyclonal antibodies directed against 5-HT. Moreover, 5-HT levels in the ovary, oviduct, uterus, and cervix were measured by high-pressure liquid chromatography with electrochemical detection. The highest 5-HT concentrations were found in the oviduct, followed in descending order by the cervix, the ovary, and the uterus. Most 5-HT-like IR was observed in the cytoplasm of mast cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
0
26
0
2
Order By: Relevance
“…Taken together, the current findings support an important role of 5-HT on the migration of sperm throughout the female tract. The possibility that 5-HT plays a role in sperm physiology may occur at 5-HT receptors and/or 5-HT transporters located on the surface of sperm, responding to the 5-HT contained in the uterine or seminal fluid (Mann et al 1961, Amenta et al 1992. However, the surprising finding that some other serotoninergic elements are intracellular remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the current findings support an important role of 5-HT on the migration of sperm throughout the female tract. The possibility that 5-HT plays a role in sperm physiology may occur at 5-HT receptors and/or 5-HT transporters located on the surface of sperm, responding to the 5-HT contained in the uterine or seminal fluid (Mann et al 1961, Amenta et al 1992. However, the surprising finding that some other serotoninergic elements are intracellular remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This PCR-based assay could also detect a minimum of 10 femtograms. These results indicate that serotonin present in embryos could arise either through synthesis by TPH2 or by transport from extracellular sources, for example, serotonin present in the tubal fluid of the oviduct (Juorio et al 1989, Amenta et al 1992, Yavarone et al 1993. The multiplicity of the mechanisms for obtaining serotonin may indicate the importance of this molecule to the embryo.…”
Section: Serotonin In Mitochondria In Mouse Embryosmentioning
confidence: 93%
“…In mammals, such studies have been lacking, though in mice, drastic effects are observed in the early embryo upon blocking tryptophan hydroxylase, the rate-limiting enzyme in serotonin synthesis. Serotonin is present in the tubal fluid of the oviduct, cervix, and uterus (Juorio et al 1989, Amenta et al 1992, Yavarone et al 1993). On administering p-chlorophenylalanine, a tryptophan hydroxylase inhibitor, to pregnant mice, it was observed that the cleavage divisions of the zygote were arrested and in cases where the embryo proceeded to the blastocyst stage, it was defective and failed to implant (Khozhai et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among the indications that 5-HT might be such a local regulator is its detection in female rodent genital tracts (Amenta et al, 1992) and in human follicular fluid (Bodis et al, 1993). Moreover, 5-HT has also been reported recently in isolated mouse oocytes and embryos (Il'kova et al, 2004;Amireault and Dubé, 2005) and in surrounding cumulus cells that also possess the rate-limiting enzyme tryptophan hydroxylase for 5-HT production, thus making these cells a potential immediate direct source of 5-HT (Amireault and Dubé, 2005).…”
mentioning
confidence: 97%